Does Reporting of Aksi Cepat Tanggap Cases Affected Public Trust on Zakat Institutions? - Pitria, Ratna Kamila; Aisy, Diamantin Rohadatul; Anggraeni, R. R. Tini (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2024)
Research Originality: Funds misallocation comitted by ACT identified as fraud and the non-transparent financial that reported in online mass online media in terms of negative reporting. This influence has never been studied on the loyalty of zakat payer (muzakki) of paying Zakat, Infaq, and Shadaqah (ZIS) in Islamic philanthropy institutions (LAZ) admidst related to negative reporting of ACT.Research Objectives: This research analyze the impact of transparency, fraud management and the cases reporting of ACT on public trust in paying zakat, infaq, shadaqah in other Islamic philanthropy institutions.Research Methods: This research setted in the Bogor City among 100 respondents of muzakki in the year 2023 and 2024. Then, multiple linear regression were involved to analyze the impact of independent variables on dependent variable.Empirical Results: The results reveal that being transparent and avoiding fraud cases will significantly increase public trust in paying ZIS at LAZ institutions. Meanwhile, coverage of the ACT cases had no impact on the loyalty of muzakki who were also well-educated.Implications: LAZ are encouraged to provide information related to ZIS funds management, so that trust of the muzakki will increase. Besides, LAZ also needs to have a strong internal control system to enforce transparency in financial reporting, and effective monitoring mechanisms to prevent fraud.JEL Classification: G23, G30, Z12